Utilization of Quizizz Platform in the Learning Evaluation Process - Muh. Putra Pratama (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the effect of using Quizizz as a learning evaluation medium to see learning success. The purpose of this study is to describe Quizizz can be used as a medium for evaluating formal learning such as exams or daily assessments, especially in mathematics lessons. This research method is qualitative analysis. Learning evaluation using quizizz helps improve the concentration of learning students. The use of quizizz can be done by lecturers who teach other subjects, teachers and students who will carry out PKM to support the industrial revolution 4.0. Research results based on questionnaires, the implementation of exams or daily assessments can be done through Quizizz by optimizing the use of features on Quizizz. Learning evaluation through Quizizz can make it easier for lecturers to conduct detailed and objective assessments. Which is seen from the percentage results of almost 90% advantages and 10% other weaknesses in their use.